Observations of the natural history and long-term outcomes of deep venous thrombosis - O'Shaughnessy, Ann M. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Anatomy, 2001)
One hundred above knee deep vein thromboses (DVT) from 89 patients (11 bilateral thrombosis) were examined to determine the dynamic status of the thrombi in the first year and to detennine the long-term clinical outcome at three years. The patients in the study included patients with a terminal illness, with a previous history of DVT or with reversible risk factors. The mortality rate in this study was 14%. The majority of deaths occurred as a result of an underlying primary disease (e.g. cancer) and 3% died from a pulmonary embolism (PE). The treatment regime followed was carried out by a number of referring physicians from different specialities, independent of any input from the Vascular Laboratory. The initial treatment regime differed among the patients. Some physicians preferred to treat with the more established regime of intravenous (IV) heparin and bed rest instead of the more recent treatment of subcutaneous low molecular weight (SC LMW) heparin and early mobility. The duration of anticoagulant therapy also varied with most physicians treating the patient for six months regardless of their risk factors. A number of symptomatic and asymptomatic events (PE’s, extension of thrombi, new DVT’s) were recorded in the follow-up period especially in the initial and late phase. The asymptomatic events were diagnosed by duplex ultrasound and it is thought that probable additional asymptomatic events may have occurred but closer time intervals between duplex ultrasound scanning would be required to document them.
Keywords: Anatomy, Ph.D.; Ph.D. Trinity College Dublin